2013
DOI: 10.1074/jbc.m113.475517
|View full text |Cite
|
Sign up to set email alerts
|

Direct Role for the Replication Protein Treslin (Ticrr) in the ATR Kinase-mediated Checkpoint Response

Abstract: Background: Treslin/Ticrr plays an important role in the initiation of DNA replication. Results: Treslin/Ticrr stimulates ATR phosphorylation of Chk1 both in vitro and in vivo. Conclusion: Treslin/Ticrr is a dual replication/checkpoint protein that directly participates in the ATR-mediated checkpoint. Significance: Identification of the essential components of the ATR checkpoint response is crucial for understanding this important signal transduction pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…25,26,[32][33][34][35][36] However, we observed that though the complex is stable in buffers of high ionic strength, it precipitated under reaction conditions necessary to measure kinase activity. Thus we were unable to test the contribution of RHINO to ATR-Chk1 signaling in vitro.…”
Section: Rhino Directly Binds To Topbp1mentioning
confidence: 42%
See 1 more Smart Citation
“…25,26,[32][33][34][35][36] However, we observed that though the complex is stable in buffers of high ionic strength, it precipitated under reaction conditions necessary to measure kinase activity. Thus we were unable to test the contribution of RHINO to ATR-Chk1 signaling in vitro.…”
Section: Rhino Directly Binds To Topbp1mentioning
confidence: 42%
“…33,40,41 We therefore made use of this methodology to further validate RHINO as a bona fide mediator of ATR-Chk1 signaling in human cells. We thus fused the cDNA encoding the Lac repressor (LacR) to the RHINO cDNA and then introduced the construct into NIH3T3 cells containing hundreds of repeats of the LacO DNA sequence.…”
Section: Tethering Of Rhino To Chromatin Activates Atr-chk1 Signalingmentioning
confidence: 99%
“…In humans, partial reconstitution reactions have been reported with ATR-ATRIP ϩ DNA (5); ATR-ATRIP ϩ ssDNA ϩ RPA (22); and ATR-ATRIP ϩ TopBP1 ϩ ssDNA ϩ RPA Ϯ Claspin with substrates that included RPA, Chk1, and p53 (23,29,37,(61)(62)(63)(64). In addition to these systems with purified proteins, a number of other in vitro systems with cell-free extracts have been reported (28, 34 -36, 65).…”
Section: Discussionmentioning
confidence: 99%
“…4A). We and others have previously shown that TICRR loss causes a DNA damage checkpoint defect, so we wanted to test whether the failure to see increased H2AX phosphorylation was due to TICRR TESE interfering with the checkpoint response (Sansam et al 2010;Hassan et al 2013). Exposure of U2OS cells with or without TICRR TESE to ionizing radiation (IR) to cause dsDNA breaks resulted in a similar increase in gH2AX foci, indicating that TICRR TESE does not interfere with H2AX phosphorylation in response to DNA damage (Fig.…”
Section: Ticrr Tese Does Not Cause Dna Damagementioning
confidence: 99%